Lane marker detection and rain removal for autonomous vehicle navigation - Li, Sihao (2019)
With the increasing need for autonomous vehicles, the driving safety of vehicles in severe weather conditions is imperative and needs to be addressed. Lane marker detection provides crucial position related information for the vehicles towards autonomous navigation. Also, lane markers detection based on machine vision is playing a crucial role in autonomous vehicle technologies nowadays. Amongst all the lane detection sensors like radar, laser, camera, etc., the camera will be the most economical and practical component to be used for testing autonomous vehicles.